2014
DOI: 10.1021/jo501076x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexane-Fused Octahydroquinolizine Alkaloids from Myrioneuron faberi with Activity against Hepatitis C Virus

Abstract: Investigation of the alkaloids from Myrioneuron faberi, a plant unique to China, gave four pairs of enantiomers (1-4). (±)-β-Myrifabral A (1) and (±)-α-myrifabral A (2) formed an inseparable mixture of anomers (cluster A), as did (±)-β-myrifabral B (3) and (±)-α-myrifabral B (4) (cluster B). Their structures were determined by X-ray diffraction and NMR analysis. Compounds 1-4 possessed novel cyclohexane-fused octahydroquinolizine skeletons and represent the first quinolizidine alkaloids from the genus Myrioneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…(Rubiaceae) as a Chinese herbal plant. These cyclohexane-fused octahydroquinolizine alkaloids exhibited inhibitory effects on hepatitis C virus [ 27 ].…”
Section: Antiviral Activities Of Alkaloidsmentioning
confidence: 99%
“…(Rubiaceae) as a Chinese herbal plant. These cyclohexane-fused octahydroquinolizine alkaloids exhibited inhibitory effects on hepatitis C virus [ 27 ].…”
Section: Antiviral Activities Of Alkaloidsmentioning
confidence: 99%
“…Compounds 28–30 inhibited replication of HCV with IC 50 values of 4.7, 2.2, and 0.9 μM, respectively, and exhibited less cytotoxicity against liver cells than the positive control telaprevir (VX-950). 41 Aloperine ( 1 ), a quinolizidine alkaloid with an unusual endocyclic ring system, was extracted from Sophora alopecuroides . Aloperine has been identified as a potent HCV inhibitor with an EC 50 value of 4.23 ± 0.99 μM.…”
Section: Extracts and Alkaloids From Plants Modulating Viral Infectiomentioning
confidence: 99%
“…(±)‐α,β‐Myrifabrals A and B were isolated as two clusters from Myrioneuron faberi in 2014. [ 24 ] The four new myrioneuron alkaloids possess a novel cyclohexane‐fused octahydroquinolizine skeleton together with a six‐membered cyclic hemiacetal. Preliminary bioactivity test indicated that both clusters exhibited promising anti‐HCV activity (IC 50 0.9 to 4.7 μmol·L –1 ) with cytotoxicity lower than that of telaprevir, a commercial pharmaceutical drug for the treatment of hepatitis C. Due to the very limited natural availability (30 mg A and 2 mg B from 30 kg dried samples), a highly efficient chemical synthesis is desirable for further SAR studies.…”
Section: Short and Scalable Total Syntheses Of Myrioneuron Alkaloidsmentioning
confidence: 99%